2016
DOI: 10.1002/eco.1767
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of beaver dams on channel hydraulics and substrate characteristics in a mountain stream

Abstract: Beaver dams have significant impacts on the hydrology, temperature, biogeochemical processes, and geomorphology of streams and riparian areas. They have also been used as a viable tool in restoring impaired riverine systems. Because of the dynamic nature of beaver dams, these influences vary and are difficult to quantify. To begin understanding the impacts of beaver dams in mountain streams, we developed 1D hydraulic models for a beaver impacted reach that includes eight dams and a non‐impacted reach to compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Two habitat types were sampled within each of the streams: (1) lotic segments directly upstream of sampled beaver ponds, which were characterised by shallow depths, cobble substrate, and fast to moderate water flow (Stout et al, 2017;Wheaton et al, 2015); and…”
Section: Study Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…Two habitat types were sampled within each of the streams: (1) lotic segments directly upstream of sampled beaver ponds, which were characterised by shallow depths, cobble substrate, and fast to moderate water flow (Stout et al, 2017;Wheaton et al, 2015); and…”
Section: Study Sitesmentioning
confidence: 99%
“…As water pools behind a beaver dam, the stream's shape forms a wide pond, characterised by slower, deeper water that might benefit swimming taxa that are excluded from fast-moving lotic reaches (Mackay, 1992;Stout, Majerova & Neilson, 2017). mobility group; MGs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beaver are ecosystem engineers and a keystone species, meaning they have a disproportionately large ecologic, geomorphic, and hydrologic effect on their environment compared with their abundance (Baker & Hill, ; Rosell, Bozser, & Parker, ). In low‐order streams, beaver build channel‐spanning dams that obstruct flow, cause backwater ponding, and decrease stream power and velocity (Naiman, Melillo, & Hobbie, ; Stout, Majerova, & Neilson, ). Decreased velocities allow for the aggradation of sediment and particulate organic matter behind dams, which raises the stream bed and reconnects incised channels with floodplains (Butler & Malanson, ; Pollock, Beechie, & Jordan, ).…”
Section: Introductionmentioning
confidence: 99%
“…Both, pools and backwaters cover deep and low velocity areas of the channel and were mainly a result of beaver dam construction. Stout et al (2016) made a comparison of the same study reach both with and without beaver dams. They concluded that there was a 50 % increase in depths and 31 % decrease in velocities for this reach when the beaver dams are present.…”
Section: Flow Depth and Velocity Frequency Distributionsmentioning
confidence: 99%